Pengaruh Literasi Keuangan Syariah dan Pemasaran Terhadap Pengambilan Keputusan Nasabah Melakukan Pembiayaan Mikro Di Baitul Mal Aceh Singkil - M. Iqbal; Mutiah Khaira Sihotang (STIKes Ibnu Sina Ajibarang, 2023)
The economic developments taking place in the world have resulted in an increasing number of financial products being offered to the public. explaining financial literacy has become increasingly complex over the last few years with the introduction of many new financial products. This requires people to have more financial knowledge to be able to address this. This is important because financial knowledge is closely related to financial behavior. Financial literacy is a component that becomes human capital that can be used in financial activities to increase the expected utility of consumption, namely behavior to increase economic welfare. The type of research used in this study is a quantitative approach. The quantitative approach is scientific research that systematically examines the parts and phenomena and their relationships. Quantitative data, namely systematic scientific research in the form of questionnaires and calculations as well as outlined in tabular form positive contribution and significant effect of Islamic financial literacy on customer decisions. From the results of the R square, which is equal to 0.770, it means that 77.0% of Islamic Financial Literacy can be explained by the customer's decision variable, while the remaining 33.0% can be explained by other variables such as education, employment status and other variables. Based on the results of previous research, the writer realizes that there are still many limitations and mistakes in this research. However, this research is expected to provide a useful contribution to the company.